2021
DOI: 10.3390/atmos12030355
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Historical Precipitation in High Mountain Asia Based on a 15-Year High Resolution Dynamical Downscaling

Abstract: The mountains of High Mountain Asia serve as an important source of water for roughly one billion people living downstream. This research uses 15 years of dynamically downscaled precipitation produced by the Weather Research and Forecasting (WRF) model to delineate contrasts in precipitation characteristics and events between regions dominated by the Indian Summer Monsoon (ISM) versus westerly disturbances during the cool season (December to March). Cluster analysis reveals a more complex spatial pattern than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Similar to Mei et al (2020) and Xue et al (2021), we showed significant improvement in precipitation and temperature accuracy as model resolution increased. In addition, we used the 4 km WRF domain from Dars et al (2021) to assess the characteristics of historical HMA precipitation (Riley et al, 2021). Importantly, our results show differences in amount, frequency, and seasonality of precipitation between valleys and the surrounding higher elevations.…”
Section: Downscalingmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar to Mei et al (2020) and Xue et al (2021), we showed significant improvement in precipitation and temperature accuracy as model resolution increased. In addition, we used the 4 km WRF domain from Dars et al (2021) to assess the characteristics of historical HMA precipitation (Riley et al, 2021). Importantly, our results show differences in amount, frequency, and seasonality of precipitation between valleys and the surrounding higher elevations.…”
Section: Downscalingmentioning
confidence: 91%
“…For example, weather stations in Nepal show mean annual precipitation of around 1,400 mm for elevations below 1 km, increasing to above 2,000 mm at an elevation of 1.6-2.4 km and decreasing to under 1,000 mm by 4 km (Krakauer et al, 2013). The north side of the Himalayas is in a rain shadow and has annual precipitation of only around 50-200 mm (International Centre for Integrated Mountain Development, 2005;Riley et al, 2021). Winter storms that propagate from the Atlantic-Mediterranean sector are a significant portion of annual precipitation in the western HMA, and are critical contributors to snowpack at high elevations further east (Lang and Barros, 2004;Riley et al, 2021).…”
Section: Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The model described in the subsequent subsection requires the following inputs from HAR: incoming radiative fluxes at the surface, 2 m air temperature, total precipitation, surface pressure, 2 m relative humidity, emissivity, and 10 m windspeed. We imposed a precipitation cutoff for drizzle at 0.25 mm per day, consistent with instrument limits on measurement (following, e.g., Riley et al, 2021). The model is driven by meteorological input from HAR and additional variables derived from them that are necessary to calculate the turbulent and outgoing longwave fluxes (e.g., surface saturation vapor pressure).…”
Section: Meteorological Inputsmentioning
confidence: 99%